The effect of patient weight and amiodarone use on the energy of a successful shock in cardioversion of atrial arrhythmias – single-center experience study. (14th October 2021) - Jiravsky, O; Rucki, L; Chovancik, J; Spacek, R; Svobodnik, A; Stepanova, R; Kubat, T; Fiala, M
Abstract: Background: Electrical cardioversion (DCCV) is an effective method of sinus rhythm restitution. Recently published data suggest higher efficiencies of higher discharge energies. The influence of individual parameters on the success of cardioversion is still studying. Purpose: To evaluate the influence of individual patient parameters on the energy of a successful external defibrillator shock during cardioversion of atrial arrhythmias Methods: The retrospective analysis cohort of all patients treated by DCCV due to atrial arrhythmias between 10/2015 and 1/2020. To evaluate potential predictors for the choice of a higher initial discharge using one-dimensional logistic regression and to include parameters significant at the 10% level of significance (p<0.1) in the multidimensional logistic regression model. Results: 1986 electrical cardioversions of 984 patients (382 repeated procedures of the same patients in a cohort). 1292 (65.1%) men and 694 (34.9%) women aged 67.0 (±10.2) years. Mean energy of the first shock 118.9 (±19.2) J with a success rate of 77.8%, energy of the second shock 154.0 (±26.3) J, which increased the overall success to 80.0%, and mean high of the third shock 173.9 (±25.6) J, when the total efficacy of DCCV in sinus rhytm restitution reached 89.8%. From the univariate binary regression, parameters significant at the 10% level of significance (p<0.1) were selected and included in a multidimensional logistic regression model. Only the patient's weight and the use of amiodarone proved to be statistically significant. Weight with OR 1.21 and use of amiodarone with OR 1.43. Conclusion: Patient weight and amiodarone use are predictors of the need to use higher energy electric cardioversion. Discussion: Amiodarone medication does not appear to increase the defibrillation threshold, but rather is a feature that represents the group of patients treated with more aggressive antiarrhythmic therapy for advanced atrial arrhythmias with more significant structural impairment, but this attitude requires further study. Funding Acknowledgement: Type of funding sources: Private hospital(s). Main funding source(s): VAVIA: IGS202009 - Racionální algoritmus při elektivní elektrické kardioverzi fibrilace síní.